Navigating the Digital Age: Empowering Kwara State University Administrators in Bridging the ICT Literacy Gap - Amura-Yusuf, Wasilat Olaide; Bolaji, Hameed Olalekan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This position paper explores the role of literacy skills, efficacy, and readiness among university administrators in Kwara State regarding the integration of Information and Communication Technology (ICT) for management functions. With the rapid advancement of technology, educational institutions are compelled to adapt to modern tools and practices for efficient management and administration. The study aims to assess the current status of literacy skills, efficacy levels, and preparedness of university administrators in Kwara State regarding the integration of ICT into various administrative tasks and functions. The research methodology involves a comprehensive survey among university administrators across various institutions in Kwara State. The findings will help educational policymakers and stakeholders develop targeted interventions and strategies to enhance capacity building, training programs, and infrastructure development initiatives. The paper also contributes to the existing body of knowledge on ICT integration in educational administration, particularly in the context of Nigerian universities. It highlights the importance of continuous professional development and training to ensure university administrators remain adept at utilizing ICT tools for effective management and decision-making. The paper advocates for targeted interventions, capacity-building initiatives, and infrastructure development efforts to enhance the ICT readiness of university administrators in Kwara State, contributing to the overall efficiency and effectiveness of higher education administration in the region.